2021
DOI: 10.3389/fpubh.2021.616456
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Acceptability of the Human Papilloma Virus Vaccine and Vaccination Among University Students in Indonesia

Abstract: Introduction: Cervical cancer, a major consequence of persistent HPV infection, is the third most common cancer in women worldwide and has claimed around 311,000 women lives in 2018. The majority of these deaths took place in low- and middle-income countries (LMICs). In LMICs, where cervical cancer screening coverage is low, the HPV vaccine is a promising tool for preventing HPV infections and, thus, averting cervical cancer cases. In Indonesia, cervical cancer is the second most common cancer and HPV vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 26 publications
5
21
1
8
Order By: Relevance
“…This study, as has been shown by other studies, found that knowledge about the vaccine, positive peer influence and promotive health worker education and recommendation regarding the vaccine were identified as promoters of vaccination uptake [ 18 , 20 23 ]. The study likewise, as has been reported elsewhere found some factors that are barriers to higher vaccine uptakes including prevailing community concerns about vaccine safety and adverse events following immunization, vaccine supply stock outs and inadequate information about vaccines [ 8 , 10 , 12 , 14 , 23 ]. Sarah et al, in their online survey conducted among 1,653 parents, found that only 28% to 54% were ready to send their children for the second dose; blaming this low uptake to child’s fear of needles, the lack of awareness about additional doses and concerns regarding vaccine safety [ 12 ].…”
Section: Discussionsupporting
confidence: 72%
“…This study, as has been shown by other studies, found that knowledge about the vaccine, positive peer influence and promotive health worker education and recommendation regarding the vaccine were identified as promoters of vaccination uptake [ 18 , 20 23 ]. The study likewise, as has been reported elsewhere found some factors that are barriers to higher vaccine uptakes including prevailing community concerns about vaccine safety and adverse events following immunization, vaccine supply stock outs and inadequate information about vaccines [ 8 , 10 , 12 , 14 , 23 ]. Sarah et al, in their online survey conducted among 1,653 parents, found that only 28% to 54% were ready to send their children for the second dose; blaming this low uptake to child’s fear of needles, the lack of awareness about additional doses and concerns regarding vaccine safety [ 12 ].…”
Section: Discussionsupporting
confidence: 72%
“…Literacy, screening, and vaccination become a practical approaches in diminishing the burden of CC. However, the KAP of Indonesian people about this issue in previous studies was poor [ 29 , 30 , 43 ]. Thereby, we aim to reevaluate the KAP towards HPV, CC, and vaccine, along with socio-demographic characteristics influences in an urban community where a massive CC prevention program has been established.…”
Section: Discussionmentioning
confidence: 99%
“…However, this topic is scarcely studied in the general population and diverse across various countries [ 25 ]. Few studies explored this topic in Indonesia in-depth: a prior study more focused on parent’s attitudes, beliefs, and uptake of the HPV vaccination [ 26 ], a study only took samples from women in single primary care about knowledge and behavior regarding CC [ 27 ], a study was conducted only in junior high school students with tiny sample [ 28 ], a study did research on women population about HPV vaccination and CC screening [ 29 ], and two studies only assessed knowledge, attitude, and acceptability of HPV vaccination among university students [ 30 , 31 ]. To the best of our knowledge, no reported data on the KAP related to HPV, CC, and vaccination among urban citizens in Indonesia, especially those reporting KAP as a united link of public health construct.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous education and monthly monitoring are needed in monitoring the diet of pregnant women during pregnancy classes at the Posyandu. In line with statement Khatiwada et al (2021) potential knowledge gaps and barriers to acceptance and help develop effective educational messages to raise awareness, reduce negativity, and promotion health services [25].…”
Section: Education Used Audio-visual Mediamentioning
confidence: 71%